Sonut (Soil Nutrition): Inovasi deteksi tanah cerdas untuk pertanian presisi masa depan - Anwar, Alif Faisal; Kamilah, Afifah Yasmin (Jurnal Teknologi Cerdas, 2025)
Agriculture plays a vital role in ensuring food security and supporting national economies. Amid global challenges such as climate change, rapid population growth, and the need for increased food production efficiency, technological innovation in agriculture is essential. One critical issue in this sector is the inability to accurately assess soil conditions affecting crop growth, leading to inefficient fertilizer use and negative environmental impacts. Soil quality is compromised by excessive fertilizer application and climate change, which also hinders farmers’ access to advanced technologies. The "SoNut" (Soil Nutrition) innovation emerges as a solution, equipped with sensors to detect and analyze soil quality based on parameters such as pH, moisture, temperature, electrical conductivity (EC), and nitrogen content. The IoT-based system sends real-time data to the cloud for accurate analysis. SoNut enables automatic identification of soil types—such as ex-mining or peat soil—providing tailored crop recommendations. Additionally, it visualizes soil quality changes across locations, empowering farmers to make informed decisions in land management, ultimately enhancing agricultural productivity and sustainability.